Burden of communicable diseases and cost of illness: Asia pacific region. (3rd July 2020) - Shah, Shahid; Abbas, Ghulam; Riaz, Nabeel; Anees ur Rehman,; Hanif, Muhammad; Rasool, Muhammad Fawad
ABSTRACT: Background: Communicable diseases such as AIDS/HIV, dengue fever, and malaria have a great burden and subsequent economic loss in the Asian region. The purpose of this article is to review the widespread burden of communicable diseases and related health-care burden for the patient in Asia and the Pacific. Areas covered: In Central Asia, the number of new AIDS cases increased by 29%. It is more endemic in the poor population with variations in the cost of illness. Dengue is prevalent in more than 100 countries, including the Asia-Pacific region. In Southeast Asia, the annual economic burden of dengue fever was between 610 and 1, 384 million, with a per capita cost of 1.06 to 2.41. Globally, 2.9 billion people are at risk of developing malaria, 90% of whom are residents of the Asia and Pacific region. The annual per capita cost of malaria control ranged from 0.11 to 39.06 and for elimination from 0.18 to 27. Expert opinion: The cost of AIDS, dengue, and malaria varies from country to country due to different health-care systems. The literature review has shown that the cost of dengue disease and malaria is poorly documented.